Rearing systems related to gastrointestinal parasites in goats from selected area in Terengganu - Hashim, Najat; Mat Yusof, Afzan (Penerbit UTM Press, 2016)
This study was the first attempt to compare the prevalence of gastrointestinal parasites in goats in three different rearing systems. A total of 287 fecal samples were randomly collected from goats in three farms in Terengganu, Malaysia. The samples were processed by using sodium chloride floatation method and observed microscopically. Out of 287 goats, 280 (97.6%) were infected with gastrointestinal parasites. Goats reared under the intensive rearing system reported the highest prevalence of infection (99%), followed by extensive rearing system (98.3%) and the lowest prevalence was reported in the goats reared under the semi-intensive rearing system (96%). The following gastrointestinal parasites were identified in goats in accordance of predominant: Eimeria spp. (89.2%), Strongyloides spp. (45.6%), Strongyle spp. (20.6 %), Moniezia spp. (13.9%) and Trichuris spp. (8.4). Three species showed predominant in goats under the semi- intensive rearing system were Strongyle spp., Strongyloides spp., and Trichuris spp. with the percentage of 33.1%, 83.1% and 10.5%, respectively. Moniezia spp. was the highest in goats under the extensive rearing system which occurred at 26.7%, whereby Eimeria spp. was predominant under intensive rearing system with the infection rate of 99%. The finding suggested that the rearing system might not influence the occurrence of GI parasites in goats. Further study should be conducted to validate this finding.